An accurate deicing method by utilizing the piezoelectric materials based on the active mode control theory. (September 2021) - Song, Zhiguang; Wei, Jiucun; Li, Fengming
Highlights: A new accurate and effective deicing method is proposed by using the piezoelectric materials. The genetic algorithm is introduced to obtain the optimal input voltages for getting deicing modes. The deicing effect of the accurate method is compared with that of the natural vibration mode method. Influences of the number and distribution of the piezoelectric patches on the deicing effects are analyzed. Abstract: Icing has a great influence on the dynamic characteristics of structures. One of an effective deicing method is to utilize the shear stresses caused by the transverse vibration of the structure, and this is usually realized by exciting the proper natural vibration mode according to the icing position. However, the natural mode cannot always be consistent with the icing position, and on the other hand, although there is vibration at the icing position, it will also cause vibration at other positions of the structure. To solve these problems, an accurate and efficient deicing method is proposed in this study. In this method, piezoelectric materials are used. They are bonded on the surface of the structure to act as the actuators. According to the icing positions, an appropriate mode shape is assumed, the peak value of which is consistent with the position of the ice. To achieve this goal, it is essential to obtain the input voltages of the piezoelectric actuators. The genetic algorithm is introduced, through which the optimal control voltage of each actuator can be found. As a result, the actual vibration of the structure will tend to the designed deicing vibration mode. Experimental and simulation results show that the present active mode control method possesses better deicing effect compared with the former natural vibration mode method. In addition, there is almost no vibration where there is no ice, which ensures the stability of the structure.